Early-Phase Urine Output and Severe-Stage Progression of Oliguric Acute Kidney Injury in Critical Care - Huang, Haoquan; Bai, Xiaohui; Ji, Fengtao; Xu, Hui; Fu, Yanni; Cao, Minghui (Frontiers in Medicine, 2021)
Background: The threshold of urine output (UO) above which the risk of severe-stage progression decreases in the early phase of acute kidney injury (AKI) remains unclear. This study aimed to investigate the association between early-phase UO and severe-stage progression of oliguric AKI and to identify an optimal UO target for guiding initial therapy among early-stage AKI patients in critical care. Methods: Adult patients with UO < 0.5ml/kg/h for the first 6 h after ICU admission (meeting diagnostic criteria of stage-1 oliguric AKI according to the Kidney Disease Improving Global Outcomes (KDIGO) guidelines) and UO ≥ 0.5 ml/kg/h in the following 6 h were identified from the Medical Information Mart for Intensive Care (MIMIC) III database. The primary outcome was progression from stage-1 oliguric AKI to stage-2 or -3 oliguric AKI according to the KDIGO criteria. We evaluated the association between early-phase (the first 6 h period after oliguric AKI) UO and AKI stage progression. Logistic regression analyses were performed to adjust for other variables, and a two-piecewise linear regression model was used to determine the threshold of early-phase UO that independently associated with AKI stage progression. Then sensitivity analyses as well as subgroup analyses were performed to assess the robustness of our findings. Results: The overall incidence of AKI stage progression was 62.5% (1614/2582) in this study. In the multivariate analysis, the early-phase UO showed significant association with AKI stage progression (odds ratio (OR), 0.38; 95% confidence interval (CI), 0.32-0.44; P<0.001). Using the two-piecewise linear regression model, a threshold of 0.8 ml/kg/h was identified, above which the risk of AKI stage progression significantly decreased (adjusted OR, 0.55; 95% CI 0.43-0.69; P<0.001). Besides, the robustness of our findings was confirmed by sensitivity and subgroup analyses. Conclusions: Among critically ill patients with early oliguric AKI, early-phase UO ≥ 0.8 ml/kg/h was independently associated with lower rate of AKI progression.